Evaluation of Pax5 expression and comparison with BLA.36 and CD79αcy in feline non‐Hodgkin lymphoma. (22nd August 2016) - Felisberto, R.; Matos, J.; Alves, M.; Cabeçadas, J.; Henriques, J.
Abstract: Paired box gene 5 ( Pax5 ) is a widely used B‐cell marker for human and canine non‐Hodgkin's lymphoma (nHL); however, in the literature there is only one case report using Pax5 in a cat B‐cell lymphoma. The purposes of this study were to investigate the expression and detection of B‐cell specific activator protein (BSAP) using a monoclonal anti‐Pax5 antibody in feline nHL (FnHL) tissue samples to evaluate its diagnostic relevance as a B‐cell marker. A total of 45 FnHL samples in 45 cats were evaluated. B‐cell lymphoma was the most common immunophenotype (51.1%) for all the samples and T‐cell the most common immunophenotype (64.3%) for the gastrointestinal (GI) form. Pax5 stained 82.6% of all B‐cell lymphomas and no expression was found in any of the T‐cell lymphomas. Anti‐Pax5 antibody staining in FnHL is similar to that reported in human and canine counterparts and may offer an excellent B‐cell marker in cats.